A description of a new genus and new species of sotol-feeding Eccritotarsini (Hemiptera: Heteroptera: Miridae: Bryocorinae) from Durango, Mexico - Menard, K. L.; Schwartz, M. D. (Zootaxa, 2018)
The new genus and species Sotolensis keltoni is described in the Eccritotarsini (Miridae: Bryocorinae) from material collected on expeditions to Durango, Mexico, by Leonard A. Kelton from the Canadian National Collection. All specimens collected were found on sotol, or Dasylirion sp. (Asparagaceae: Nolinoidae). Habitus images and images of the female and male genitalia are included, and a discussion of genital structure evolution is discussed.